Application of andiroba oil as a novel collector in apatite flotation. (July 2022) - Santos, Leandro Henrique; Otávio dos Santos, Guilherme; Fernandes de Magalhães, Luciano; Rodrigues da Silva, Gilberto; Eduardo Clark Peres, Antônio
Graphical abstract: Highlights: Andiroba oil is mainly composed of oleic and palmitic acids. Andiroba oil collector presents lower CMC than that of pure sodium oleate collector. Andiroba oil collector shows greater selectivity in the separation of apatite from carbonates at pH 7.5. Longer conditioning times with Andiroba oil collector favour the recovery apatite while impairing the recovery of calcite and dolomite. Abstract: Phosphate ores are highly complex, requiring sophisticated processing steps to meet the specifications of the fertilizer industry. Froth flotation is widely used in several phosphate ore concentration routes, using vegetable-origin fatty acid salts as collectors. In this scenario, the search for alternative sources with high accessibility, efficiency, and availability becomes strategic. In this work, Andiroba oil ( Carapas guianensi ) was evaluated regarding its physicochemical characteristics (fatty profile, acidity, saponification, and iodine indices) and the performance of its fatty acid salts as a selective apatite collector in the flotation from calcium and magnesium carbonate gangue minerals, commonly found in phosphate ores. The oil sample was found to be mainly composed of oleic and palmitic acid. The best selectivity between apatite and carbonates was obtained at pH 7.5 and 20 mg.L −1 collector concentration, especially for the apatite-dolomite system. The zeta potential and FTIR results indicated that chemisorption and precipitation of calcium salts were the collector adsorption mechanism responsible for hydrophobization. The selectivity achieved was attributed to the difference in the conformation of the hydrophobic layers formed on the surface of each mineral, being related to the spatial arrangement and density of active sites. Andiroba oil proved to be promising as an apatite collector in flotation systems with carbonate gangue, being an environmentally attractive alternative for the phosphate industry.